Silencing of Long Non-coding RNA NEAT1 Upregulates miR-195a to Attenuate Intervertebral Disk Degeneration via the BAX/BAK Pathway - Tang, Ning; Dong, Yulei; Liu, Jiaming; Zhao, Hong (Frontiers in Molecular Biosciences, 2020)
Background/Aims An increasing body of evidence has demonstrated that long non-coding RNAs (lncRNAs) play a vital regulatory role in intervertebral disk degeneration (IVDD). Nucleus enriched abundant transcript 1 (NEAT1), a novel cancer-related lncRNA, is associated with many malignancies, including ovarian cancer, and esophageal squamous cell carcinoma. Nevertheless, the role of NEAT1 in the progression of IVDD remains to be studied. Here, we explored the effect of NEAT1 on the progression of IVDD and the mechanisms involved. Methods An IVDD model was constructed in SD rats in vivo, and degeneration was induced by advanced glycation end product (AGE) in human nucleus pulposus cells (HNPC) in vitro. Quantitative real-time PCR was performed to detect the relative NEAT1 and miR-195a expressions and further confirmed the relationship between NEAT1 and miR-195a. Cell apoptosis was evaluated by TUNEL assay. The related mechanisms were explored by Western blot assay. Results The relative NEAT1 expression was significantly upregulated in the IVDD rat model and the denatured HNPC. Silencing of NEAT1 expression in HNPC significantly promoted the Collagen II and TIMP-1 expression induced by AGE while greatly suppressing the expressions of MMP-3 and cleaved caspase-3. Besides, downregulation of NEAT1 obviously reversed the AGE-induced apoptosis in HNPC. More interestingly, these effects of NEAT1 knockout on HNPC were largely reversed by silencing of miR-195a or overexpression of BAX under the AGE treatment. Mechanically, the direct combination of NEAT1 with miR-195a resulted in upregulation of MMP-3, cleaved caspase-3, BAX, and BAK, as well as downregulation of Collagen II and TIMP-1, which are associated with EMT and apoptosis. We also demonstrated similar results in the in vivo experiments. Conclusion NEAT1 played its role in IVDD progression via partly by mediating the miR-195 expression and might be used as a potential target for IVDD therapy.